The witch of Portobello - Coelho, Paulo (Thorsons, an imprint of HarperCollins Publishers, 2007)
How do we find the courage to always be true to ourselves--even if we are unsure of whom we are? That is the central question of international bestselling author Paulo Coelho's profound new work, The Witch of Portobello. It is the story of a mysterious woman named Athena, told by the many who knew her well--or hardly at all.